Comparison of agarwood essential oil & water soluble (hydrosol) - Fairul Idzwan, Mohd (2008)
Gaharu which is also known as Aquilaria is the most valuable wood in the world with higher prices and demands nowadays. The widely uses of gaharu in meditation field, essential oil production and etc makes gaharu one of the precious things on earth. For last several years, many methods were founded to extract gaharu especially spesifically in distillation. Methods such as steam distillation and spinning band distillation were discovered but the most common methods which more precise and saving cost was hydrodistillation. In this study, we use Aquilaria Maleccencis from Malaysia as the sample and it can be classified in grade C. This method requires temperature according to water boiling point which is 100 OC and gaharu sawdust size less than 1.0mm. After extraction, analysis was carrying out by using gas chromatography mass spectrometer to see the component in oil sample. To get the secondary oil, 2 different kind of solvent (ethyl acetate and hexane) were used to trap gaharu essential oil component by mix it with hydrosol which left in the flask. This step is carry out by going through several processes such as centrifuge, filtering and water termination. Then, primary oil and secondary oil is analysis to see compounds which contain in the sample. As the conclusion, we have founded several compounds in secondary oil which same as primary oil and this mean the water can be used to recycle in the next distillation process